Dynamics of youth unemployment in ASEAN-5 emerging economies through macroeconomic analysis - Othman, Kamarudin; Mustapha, Yanti Aspha Ameira; Zakaria, Zaherawati; Salehhin, Muhamad Amirul (Asian Journal of Empirical Research, 2024)
This research investigates youth unemployment dynamics in ASEAN-5 emerging economies using a macroeconomic framework. Employing the panel Autoregressive Distributed Lag (ARDL) methodology, it examines the effects of Gross Domestic Product (GDP), inflation rate, population growth and Foreign Direct Investment (FDI) on youth unemployment rates. Empirical results reveal that GDP and inflation significantly influence youth unemployment over the long term. This highlights the interplay between economic expansion and youth employment prospects. Conversely, neither population growth nor FDI significantly impacts youth unemployment. This suggests that increasing population or attracting foreign investments alone may not directly translate to better employment opportunities for the youth. Instead, robust economic growth and stable inflation rates are crucial. These findings underscore the need for ASEAN-5 policymakers to develop strategies fostering economic growth and controlling inflation to mitigate its adverse effects on youth employment. The research provides insights into how targeted economic policies can better address youth unemployment challenges, creating a conducive environment for job creation and economic stability, ultimately benefiting the youth workforce.